A systems biology approach to identify microRNAs contributing to cisplatin resistance in human ovarian cancer cells. Issue 11 (1st September 2017) - Liu, Weisha; Wang, Shuyuan; Zhou, Shunheng; Yang, Feng; Jiang, Wei; Zhang, Qingyuan; Wang, Lihong
Abstract : The dysregulated microRNAs contribute to cisplatin resistance in ovarian cancer cells. Abstract : Cisplatin (CDDP)-based chemotherapy is a standard first-line therapy for ovarian cancer. However, drug resistance remains a major obstacle to its efficacy. Recently, increasing evidence suggested that the aberrant expression of microRNAs (miRNAs) may contribute to drug resistance. Here, we proposed a systems biology analysis strategy to identify the novel miRNAs potentially involved in CDDP resistance in human ovarian cancer cells. Firstly, we identified the candidate miRNAs associated with CDDP resistance using NCI-60 data. Next, the differentially expressed genes (DEGs) in the CDDP-resistant ovarian cancer cell line OVCAR-8R were obtained. After mapping the DEGs to a human protein–protein interaction network, a CDDP resistance-related sub-network for ovarian cancer was constructed, and subsequently the functional gene modules were identified. Then, based on the experimentally validated miRNA regulations to target genes, 4 candidate miRNAs (miR-24-3p, miR-192-5p, miR-139-5p and miR-155-5p) were identified to potentially contribute to ovarian cancer cell chemoresistance to CDDP through mediating OVCAR-8R cell CDDP resistance-related gene modules, which participated in functions that were closely related to "apoptosis", "cell cycle" and "adhesion". In addition, we predicted the therapeutic drugs that might reduce or reverse CDDP resistance by targeting these 4 identified miRNAs. This study revealed the underlying mechanism of CDDP resistance, and provided novel potential drug targets and therapeutics for CDDP-resistant ovarian cancer patients.